Bone morphogenetic proteins in the bovine oviduct: Differential expression of BMP-5 in the isthmus during the estrous cycle - Garcia, Elina Vanesa (2014)
Bone morphogenetic proteins (BMPs) play a crucial role in mammalian reproduction, but little is known about their expression and function in the oviduct, where preimplantation events take place. In the present study, messenger RNA (mRNA) expression of BMPs was examined by semiquantitative reverse transcription-polymerase chain reaction (RT-PCR) in bovine oviduct epithelial cells obtained from ampulla and isthmus at different stages of the estrous cycle. Expression of BMP-2, -3, -4, -7, -10 and -15 mRNA was detected in epithelial cells of both anatomic regions, whereas BMP-5 mRNA was specifically expressed in isthmus epithelial cells throughout the estrous cycle. High expression levels for BMP-5 and for BMP-2, -4, and -7 mRNA were observed during the preovulatory stage. Considering the region-specific gene expression of BMP-5, its protein localization in the oviduct and its presence in the oviductal fluid were evaluated by immunohistochemistry and Western blot analysis. BMP-5 protein staining was observed in isthmus sections with a more intense signal in the luminal epithelial cell layer. In addition, a 21 kDa protein corresponding to the BMP-5 mature monomeric form was detected in bovine oviductal fluid throughout the estrous cycle. In conclusion, these results demonstrate that different members of the BMP family are expressed in the bovine oviduct during the estrous cycle, and reveal that BMP-5 is differentially expressed in the isthmus. The expression of this factor in the oviduct epithelium and its presence in the luminal fluid suggest a possible action of BMP-5 as a new autocrine and/or paracrine regulator of the reproductive events that occur in the bovine oviductal environment.